The Future of Renewable Energy in Iraq: Potential and Challenges - Omar Sharaf Al-Deen Al-Yozbaky; Saraa Ismaeel Khalel (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Renewable energy (RE) is currently viewed as a planned and effective option to achieve development sustainability, as it provides an appropriate answer to climate change and also meets the power requirements. With regards to the current scenario in Iraq, a grave deficit with regards to electric power has been looming in the country and this serious shortage in equipped power started decades ago. Various prospects exist regarding the adoption of renewable energy in order to deal with the current issue pertaining to power shortage. This present study is a crucial examination of the existing and future electrical power needs in Iraq and the ongoing planning and challenges that are deliberated, for a better understanding of the prospects of utilizing Renewable energy sources for investment as well as to be able to provide energy to all those who need it in Iraq. Hopefully, this study can support researchers in earning an in-depth understanding of previous research efforts on this subject, and in exploring directions for future research.